Factors Supporting Breastfeeding among Working Women in the Workplace: A Systematic Review of Qualitative Studies - Azizah Noor; Denny Hanifa Maher; Adi Mateus Sakundarno; Sulistiyani Sulistiyani (BIO Web of Conferences)
Breast milk is the best food for babies, containing all the energy, nutrients, and antibodies needed to protect the body from disease. Although the WHO recommends breastfeeding for only 6 months, working women have less potential to breastfeed exclusively than non-working. This is because most working women stop breastfeeding when returning to work after maternity leave. Therefore, this study aimed to identify factors that support breastfeeding in the workplace. This study applied systematic review using the PRISMA method and the data were obtained from PubMed, Science Direct, and Scopus searches. The literature review used full-text published from 2014 to 2024 and qualitative original articles that were not from review. A qualitative study checklist was carried out using the Joanna Briggs Institute critical appraisal tool obtained 14 articles. The results showed that both internal and external factors played a significant role in exclusive breastfeeding. These included maternal determination, previous breastfeeding experience, proper knowledge about exclusive breastfeeding, as well as family, and partner support. External factors included workplace policies, such as maternity leave, availability, accessibility of safe, comfortable lactation facilities, on-site daycare, breastfeeding education, and lactation counseling. Additional external support from colleagues, employers, healthcare staff, and caregivers also played a significant role in exclusive breastfeeding. The success of breastfeeding among working women was significantly influenced by internal factors and immediate support system, as well as external workplace factors, policies, and support from colleagues and superior.